The Many Faces of Communication Quality - Kastberg, Peter (Language at Work - Bridging Theory and Practice, 2006)
When it comes to quantity, you can easily measure and quantify, the length of an instructional text, the number of words and images used in an ad, or the duration of a sales presentation etc.There is nothing, however, in such a purely quantitative measurement that will tell you whether or not the text, the ad and the talk were “good”. A “good” instructional text is not necessarily a short one, the text to image ratio of an ad says nothing about how effective the ad may be, and a compressed talk will often leave the inquisitive listener unsatisfied.